BRIDGING DIGITAL TOOLS AND SCIENTIFIC LITERACY: A SYSTEMATIC REVIEW ON INQUIRY-BASED LEARNING APPROACHES - Azneezal Ar-Rashid Mohd Ramli; Mohamad Termizi Borhan (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
This systematic review meticulously explores the incorporation of digital tools within inquiry-based learning (IBL) frameworks to enhance scientific literacy, addressing pivotal questions concerning effective, digitally enabled educational strategies. Specifically, the study investigates (1) how digital tools support the effectiveness of IBL across diverse educational contexts, (2) the ways in which IBL enhances scientific literacy at various educational levels, and (3) the impact of innovative and hybrid IBL approaches on student engagement and understanding in scientific subjects. Adhering to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to ensure methodological rigor and transparency, this review synthesizes empirical research published between 2020 and 2024, initially identifying 389 articles from Scopus and Web of Science databases, with 35 meeting stringent inclusion criteria. The analysis reveals that the incorporation of digital tools, for example, simulation software, collaborative platforms, and gamified learning environments—within IBL significantly transforms scientific literacy by fostering critical thinking, student engagement, as well as collaborative skills. Furthermore, the adaptability of IBL across diverse educational settings, complemented by gamification and culturally relevant methodologies, facilitates greater accessibility and inclusivity in science education, thereby preparing students for academic success and informed participation in a scientifically literate society. Despite the evident transformative potential of digital tools in advancing scientific literacy, the review underscores the necessity for further research to optimize their implementation, particularly within underrepresented and varied educational contexts. This comprehensive synthesis contributes to the discourse on educational technology by providing critical insights and delineating future research directions aimed at cultivating a scientifically literate generation through digitally empowered IBL.